Proof: Simplify 4

Let's prove the following theorem:

(a + b) + (b ⋅ (-1)) = a

Proof:

View as a tree | View dependent proofs | Try proving it

Proof Table
# Claim Reason
1 a + (b + (b ⋅ (-1))) = a a + (b + (b ⋅ (-1))) = a
2 a + (b + (b ⋅ (-1))) = (a + b) + (b ⋅ (-1)) a + (b + (b ⋅ (-1))) = (a + b) + (b ⋅ (-1))
3 (a + b) + (b ⋅ (-1)) = a if a + (b + (b ⋅ (-1))) = a and a + (b + (b ⋅ (-1))) = (a + b) + (b ⋅ (-1)), then (a + b) + (b ⋅ (-1)) = a
Previous Lesson Next Lesson

Comments

Please log in to add comments